Fathers’ Sensitivity in Infancy and Externalizing Problems in Middle Childhood: The Role of Coparenting - Jacobvitz, Deborah; Aviles, Ashleigh I.; Aquino, Gabriela A.; Tian, Ziyu; Zhang, Shuqi; Hazen, Nancy (Frontiers in Psychology, 2022)
The present study examined the role of father sensitivity and couple coparenting quality in the first 2 years of life in relation to the development of externalizing behavior problems in middle childhood, focusing on the unique role of fathers. In this study, 125 mothers, fathers, and their first-born children were followed from 8 months to age 7 years. Paternal sensitivity was rated when infants were 8 and 24 months old. Fathers were videotaped at home playing, feeding, and changing their 8-month-old infants’ clothes. They also were videotaped in a lab playing with their 24-month-olds and solving a variety of challenging tasks. At 24 months, competitive coparenting was assessed via videotaped triadic family interactions at home in which families participated in a variety of tasks (i.e., clothes change, eating a snack together and solving tasks). Teachers rated externalizing behavior problems when the children were age 7. Continuity in paternal sensitivity was documented from 8 to 24 months, and paternal sensitivity at 8 months predicted externalizing behavior in middle childhood through father sensitivity at 24 months. Moreover, paternal sensitivity at 8 months predicted competitive coparenting which, in turn, forecast externalizing behavior problems in middle childhood, even after controlling for maternal sensitivity at 8 and 24 months. These findings highlight the unique role of paternal caregiving quality during the first year of life on couple coparenting and children’s subsequent development of externalizing problems and have implications for creating effective interventions to prevent children from developing externalizing disorders.